Penerapan Model Pembelajaran Pair-Checks Pada Pembelajaran IPAS - Asti Kurnia Dewi Saputri; Dedy Firduansyah; Sujarwo (STAI AL-AMIN, 2025)
Education is an essential means of improving the quality of human resources to ensure the continuity of a nation. The use of appropriate learning models can foster students’ enjoyment of a subject, thereby increasing their motivation to complete assignments and making it easier for them to understand the lesson, which in turn leads to better learning outcomes. The Pair-Checks learning model is one of many strategies that teachers can implement to improve the quality of instruction. This study uses an experimental method with a quantitative approach, aiming to test the effect of a treatment on another variable under controlled conditions. Based on the research findings, the learning outcomes of fifth-grade students at SDN 2 Tugu Sempurna in the subject of IPAS (Integrated Science and Social Studies) reached the expected level after the implementation of the Pair-Checks learning model.